The Effectiveness of Initiation Response Evaluation Strategy in Teaching Students’ Reading Comprehension - Kardi Nurhadi (Journal of English Language Learning, 2017)
Abstract The purpose of this research is to know the effectiveness of Initiation Response Evaluation strategy effective in teaching reading comprehension. The formulation of problem is: Is Initiation Response Evaluation strategy effective in teaching reading comprehension? To achieve the purpose, the writer used Initiation Response Evaluation Strategy in teaching students’ reading comprehension. According to Franke et al (2007:1), “ Initiation Response Evaluation the teacher gives the questions, and then the students’ response the questions, and then the teacher evaluates the response”. In conducting the research, the writer used pre-experimental as the research method. In pre-experimental method, the writer used one group pretest and posttest. The research was conducted at the tenth grade of students SMAN 2 Indramayu. After the writer collected and analyzed the data, it was concluded that Initiation Response Evaluation was effective in teaching students’ reading comprehension of narrative text. It was proved by the score of tcount was higher than ttable. the value of tcount was 18,4 while the value of ttable at 0,05 level two tiled was 2.042. it means that tcount  >  ttable or in other word, null hypothesis (Ho) was rejected and alternative hypothesis (Ha) was accepted. Finally, the writer hoped that the result of this research will give English teacher an alternative strategy in teaching reading comprehension of narrative text. Keywords : Reading comprehension, Initiation response evaluation strategy, narrative text, pre-experimental.